To hell and back: Carlo Porta’s inversion of Dante’s Inferno - Luciano, B (Spunti e Ricerche, 2016)
In the major critical biography of the nineteenth-century Milanese poet Carlo Porta, Guido Bezzola insists that Dante’s true greatness escaped Porta because he lacked the religious component which is central to Dante and without which Dante cannot be understood. (p. 62) While it is true that Porta’s incomplete parodic translations from Dante’s Inferno lack that religious element, Porta displays his genuine understanding of and appreciation for the Tuscan master by transporting Dante successfully into his era through brilliant transmutations, modernisation, and subversion of Dante’s masterpiece.